A prática do Fanadu sob ponto de vista das mulheres : uma análise a partir do bairro de Cuntum Quelélé - Monteiro, Nadesda Augusto (2023)
In Guinea-Bissau, fanadu signals a turning point in the lives of those who have undergone it. The practice is signalled as a rite of passage to adulthood, the appropriate phase for its occurrence is between the ages of 15-17, the phase in which girls say goodbye to adolescence for adulthood. This paper analyses the practice of fanadu in Guinea-Bissau. This work aims to analyse the meaning of fanadu in the lives of women who have undergone the procedure. Specifically, we aim to, among other things, 1. Identify, from their speeches, how the practice of fanadu has impacted (negatively and/or positively) their lives; 2. Understand whether fanadu really interferes in the sexual and maternal life of women subjected to the practice and, finally, 3. Investigate whether in their views fanadu is really perceived as a form of violence. In this work, we adopted a qualitative research methodology, based on semi- structured interviews that took place in the neighbourhood of Cuntum quelélé with twenty- five female participants. Many studies consider it an ancient practice, generally as a tradition from the point of view of the practitioners, but it also involves controversies and various discussions about the female body, this because part of its ritual involves cutting the clitoris. In Guinea-Bissau, the practice is mostly common in Islamised ethnic groups, although there are women from non-Islamised ethnic groups who undergo the ritual, these are usually those who go by free will, by conversion to Islam or even by the influence of colleagues. The justifications for their permanence are varied, one of the most common is related to the hygiene issue of girls, one of the main results of this work is related to violence, a subject little discussed and taken into account in the Guinean context. In addition, the work had other results such as interpretation of the meaning of fanadu linked to the notion of tradition, community and friendship.